2006
DOI: 10.1111/j.1741-4520.2006.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory infections during pregnancy and congenital abnormalities: a population‐based case‐control study

Abstract: Diseases of respiratory system caused by acute infections are among the most common maternal diseases during pregnancy. The objective of the study was to estimate the association between congenital abnormalities and acute respiratory infections during the first trimester of pregnancy. The data set of the Hungarian Case-Control Surveillance of Congenital Abnormalities including 22 843 cases with congenital abnormalities, 38 151 population controls without congenital abnormalities and 834 malformed controls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…These results support previous studies that reported an increased risk of birth defects following an illness usually associated with fever (Zhang and Cai, 1993;Acs et al, 2005Acs et al, , 2006aAcs et al, , 2006b. Of interest is a recent set of studies analyzing data from the Hungarian Congenital Abnormalities Registry (HCAR; Acs et al, 2005Acs et al, , 2006aAcs et al, , 2006b.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results support previous studies that reported an increased risk of birth defects following an illness usually associated with fever (Zhang and Cai, 1993;Acs et al, 2005Acs et al, , 2006aAcs et al, , 2006b. Of interest is a recent set of studies analyzing data from the Hungarian Congenital Abnormalities Registry (HCAR; Acs et al, 2005Acs et al, , 2006aAcs et al, , 2006b.…”
Section: Discussionsupporting
confidence: 87%
“…Of interest is a recent set of studies analyzing data from the Hungarian Congenital Abnormalities Registry (HCAR; Acs et al, 2005Acs et al, , 2006aAcs et al, , 2006b. These studies used a large dataset to evaluate the associations among maternal cold (Acs et al, 2006a), maternal influenza (Acs et al, 2005), maternal acute respiratory illnesses (ARI) (including bronchitis, sinusitis, pharyngitis, etc.)…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies have shown that influenza and in particular a fever (hyperthermia) associated with the influenza may play an etiologic role in the origin of orofacial clefts (Acs et al, 2006;Metneki et al, 2005). One study found that there was a decrease in the prevalence of orofacial clefts among women with influenza who took an antifever medication; when folic acid was taken in addition to the antifever medication, a preventative effect was seen (Acs et al, 2005).…”
Section: Discussionmentioning
confidence: 99%